2012
DOI: 10.1186/1471-2369-13-96
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study on the association between acute renal failure (ARF) and the duration of polypharmacy

Abstract: BackgroundBecause of the rapid growth in elderly population, polypharmacy has become a serious public health issue worldwide. Although acute renal failure (ARF) is one negative consequence of polypharmacy, the association between the duration of polypharmacy and ARF remains unclear. We therefore assessed this association using a population-based database.MethodsData were collected from the Taiwan National Health Insurance Research Database (NHIRD) from 2003 through 2006. The case group included patients hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Doctor-shopping can signal problems of healthcare system and drug overuse resulting in worsening of health condition of doctor-shoppers. A negative impact of polypharmacy on health has been well documented in the literature [49]. Also, changing doctors reduces continuity of care which can translate into worse disease management and increased waiting times as well as increased cost of treatment for both the patients and payers [50].…”
Section: Discussionmentioning
confidence: 99%
“…Doctor-shopping can signal problems of healthcare system and drug overuse resulting in worsening of health condition of doctor-shoppers. A negative impact of polypharmacy on health has been well documented in the literature [49]. Also, changing doctors reduces continuity of care which can translate into worse disease management and increased waiting times as well as increased cost of treatment for both the patients and payers [50].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was shown that the simultaneous administration of at least two cardiovascular drugs (antihypertensive agents, antiarrhythmic agents, diuretics, platelet aggregation inhibitors, lipid‐lowering agents and digoxin) was significantly associated with an increased risk of AKI . Similarly, a study of the large Taiwan National Health Insurance Research Database found that polypharmacy for 31–90 days, 91–180 days and over 181 days was respectively associated with odds ratios for developing acute kidney failure of 1.33 ( P < 0.001), 1.65 ( P < 0.001) and 1.74 ( P < 0.001), when compared with polypharmacy for less than 30 days .…”
Section: Discussionmentioning
confidence: 99%
“…Polypharmacy has been linked to poor health outcomes in this population including increased risk for AKI, falls, and functional decline. 14,15 Each of these potential causes of AKI is discussed in the following section of this paper.…”
Section: Causes For Akimentioning
confidence: 99%
“…15 Polypharmacy is emerging as a significant contributor to poor health outcomes in older adults such as increased risk of hospitalization, greater chance of adverse drug reactions, and higher health care costs. 21,22 The most frequent adverse drug reaction in critical care is drug-induced AKI, and cardiovascular medications pose the highest risk.…”
Section: Polypharmacymentioning
confidence: 99%
See 1 more Smart Citation